Asia - Oachs, Emily Rose (Minneapolis, MN : Bellwether Media, 2016)
Simple text and full-color photography introduce beginning readers to Asia.
The largest continent -- Where is Asia? -- The land and climate -- The plants and animals -- The people -- Fast facts about Asia -- Glossary -- At the library.
Includes bibliographical references (page 23) and index.
2.9
K-3
Keywords: Asia; Asia; Readers (Elementary)